User Interface Design Aplikasi Mobile Hola-Hola - Muhammad Divo Yursal; Dwi Mutia Sari (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The background for the design of the user interface for the Hola-Hola mobile application is the problems that exist in the Hola-Hola premium gadget accessories business. Namely the limited space for product sales in businesses, which only provide offline services, so marketing is not effective and results in product sales being relatively low. This design uses the "Design Thinking" method with a user-focused approach, as well as "S.W.O.T" as a data analysis method, and uses the elements and principles that exist in U.I. Design and visual communication design in general. This application functions as a forum for conveying information about products and services, and user transactions, as well as a feature called "custom case", which is designing case designs directly through the application. The output of this design is an application prototype, aiming to see the user flow in the application later, as well as supporting media that have their respective functions. From the feasibility tests that have been carried out on several targets, a positive response has been received in terms of interface appearance as well as existing functions and features. Fresh appearance, the message conveyed and the flow is clear. The custom case feature is the main attraction for users, and the placement of sales features needed by Hola-Hola is in one application, so this application is expected as a business strategy for businesses, in increasing and expanding marketing.